DESAIN INTERIOR DAN MINAT KUNJUNG MASYARAKAT DI PERPUSTAKAAN DAERAH KABUPATEN TRENGGALEK - Itsna Dewi Larasati; Prisca Budi Juvitasari (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Interest in visiting the public at the Trenggalek regional library is still relatively low. One of the important factors that can increase the interest in visiting and the comfort of the community is interior design. This study aims to determine the role of interior library design in increasing user interest in visiting and knowing the condition of the library based on the elements of interior library design. This study uses a qualitative method with purposive sampling technique as a way of searching for informants. The informants in this study consisted of 3 informants, namely 2 users who had visited the Trenggalek regional library before and before, and 1 librarian. Researchers used data collection techniques in the form of observation, interviews, and documentation. The presentation of the research is done in the form of a narrative text. The results of this study indicate that the interior design of the Trenggalek regional library has a good influence on efforts to increase public interest in visiting. There are several elements that have been implemented well, including layout, color, and lighting. However, there are still unsatisfactory elements, namely air circulation and sound system. This is due to the small number of fans, the absence of air conditioning, and a whispering sound is still heard. The interior design of the Trenggalek regional library is not optimal due to the limited cost of building a library. Meanwhile, several factors in the interest of visiting are service, infrastructure, attractiveness of the place, and security.